2021
DOI: 10.3390/jcm10091879
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life and Sleep in Patients with Pituitary Adenoma in Relation to Tumor Type and Compression of the Optic Chiasm

Abstract: Objective: To determine the effect of transsphenoidal surgery on quality of life and sleep in patients with pituitary adenomas depending on tumor type and compression of the optic chiasm. Methods: In this prospective study, patients with pituitary adenomas who were scheduled for transsphenoidal surgery completed the Short Form 36 Questionnaire, Pittsburgh Sleep Quality Index, and Epworth Sleepiness Scale preoperatively and 7.5 (±1.5) months after surgery. Patients were analyzed based on tumor type and compress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 43 publications
0
7
2
Order By: Relevance
“…These symptoms might be more under control due to hormonal excess after surgery being reduced. However, alleviation of sleep disturbances after tumor surgery has been discussed controversially ( 16 18 ) and though we could see an improvement after surgery in the Knosp classification, Hardy's extrasellar growth classification did not yield significant differences.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…These symptoms might be more under control due to hormonal excess after surgery being reduced. However, alleviation of sleep disturbances after tumor surgery has been discussed controversially ( 16 18 ) and though we could see an improvement after surgery in the Knosp classification, Hardy's extrasellar growth classification did not yield significant differences.…”
Section: Discussioncontrasting
confidence: 54%
“…These symptoms might be more under control due to hormonal excess after surgery being reduced. However, alleviation of sleep disturbances after tumor surgery has been discussed controversially (16)(17)(18) and though we could see an improvement after surgery in the Knosp classification, Hardy's extrasellar growth classification did not yield significant differences. Although Hardy's suprasellar growth classification describes the compression of the optic chiasm better than Knosp, we did not observe significant differences between the grades A-B and C-E regarding SNH.…”
Section: Discussioncontrasting
confidence: 53%
“…Previous studies (De Nys et al, 2022; Leistner et al, 2015) have reported abnormal sleep function and fatigue in patients with nonfunctional macroadenoma 1–18 years after operation, which is different from our findings, which may be associated with population and sample size differences. The larger size of the adenoma oppresses the injured SCN site and thus affects the circadian rhythm, but the subjects are all patients with nonfunctional macroadenoma, and the postoperative course is larger (Sagan et al, 2021). Whether pituitary adenomas disease or treatment itself impairs sleep or natural ageing causes sleep abnormality, remains to be investigated by future studies.…”
Section: Discussionmentioning
confidence: 99%
“…As reported by Arnold et al ( 2009 ), pituitary tumour overall 5‐year recurrence rate is 7%–35%, a simple surgical recurrence rate is 45%–75%. High recurrence rate in patients with the disease and other conditions lead patients to take resignated coping, with incline to adopt the powerless and fatalistic attitude, it may potentially exert an important impact on the quality of life, treatment compliance, doctor‐patient and nurse–patient communication, also it is not conducive to treatment and rehabilitation of patients with the disease (Okati‐Aliabad et al, 2022 ; Sagan et al, 2021 ). Medical workers should be concerned about the problem of recurrence in patients with pituitary tumours, pay more attentions to the life attitude and mental state of recurrent patients (Zhang et al, 2021 ; Zhu et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%